Penerapan Service Quality Dalam Upaya Menjaga Citra Bank Terhadap Loyalitas Nasabah Di Bank Sumut Syariah Kcp Binjai - Novitri Ramadhani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Service quality, known as service quality, is an important factor in the banking business as an effort to increase customer satisfaction. The higher the perceived level of service quality, the greater the increase in consumer satisfaction. This research aims to explain the implementation of service quality implemented by Bank Sumut Syariah Kcp Binjai in an effort to maintain its image to customers. This research method uses literature study by collecting and reviewing sources related to the title such as journals, books and others. A bank's image can be good in the eyes of the public if the services provided by the bank can satisfy its customers